El rompecabezas incompleto. La omisión normativa y jurisprudencial sobre la protección por el derecho de autor de personajes y objetos de la obra - Murillo Chávez, Javier André (2015)
This article analyzes the missing rule and ruling about the protection of characters and fictional objects which are part of works covered by copyright. The author systematizes the criteria used in the administrative jurisprudence for conflicts between the intellectual property and the industrial property to extract specific rules in cases that involve fictional objects and characters, establishing and proposing criteria to find out the originality of these elements.